DUNIA PENUH DENGAN TIPUAN (Telaah atas Konsep al-Gurur dalam al-Qurâ€™an) - Abdul Kallang (AN-NISA, 2017)
This paper examines the world is full of trickery review of the concept of al-Gurur in the Qur'an. This paper discusses the tendency of most people to be deceived by the life of almost instantaneous. Religion is a system of values that are recognized and believed to be true because the road to survival. Disbelievers are those who do not follow the rules of the truth that has been determined in religion, so that al-Gurur is a challenge for people who embrace the challenge for those who follow the formula of truth, the challenge for those who are obedient and faithful to the rule safety. Al-Gurur are thorns that are destroying the human life. Â Religion as divine rules that can control the people who have common sense voluntarily to the good fortune of living in the world and in the hereafter. Therefore Al-Gurur is a mental illness that is misleading because of a trick of the devil. trap someone in the destruction and devastation of their own desires.